Liquid Crystals: Polymer‐Stabilized Micropixelated Liquid Crystals with Tunable Optical Properties Fabricated by Double Templating (Adv. Mater. 37/2017). Issue 37 (4th October 2017) - Sasaki, Yuji; Ueda, Motoshi; Le, Khoa V.; Amano, Reo; Sakane, Shin; Fujii, Shuji; Araoka, Fumito; Orihara, Hiroshi
Abstract : A micropixelated liquid‐crystal (LC) structure consisting of topological defects is stabilized by photopolymerization. In article number 1703054, Yuji Sasaki and co‐workers demonstrate that by immersing the polymer‐stabilized sample directly into another LC solvent, the polymer network imprints the infiltrating LC molecules without deteriorating the original structure. The replaced molecules enhance the retardation and remain responsive to external stimuli.